Ethics and innovation : 10 years WIPO Ethics Office (World Intellectual Property Organization, 2020)
"This publication brings together information on WIPO's Ethics Office and the thinking of leading ethicists on ethics and innovation, culture and justice as presented in the WIPO Public Lecture Series." --